In vitro comparison of the immediate adhesive strength in dentin of three universal adhesive systems - Acurio-Benavente, Mariana (2018)
Objective: To compare the adhesive strength in dentin of three universal adhesive systems in vitro by means of the shear test. Materials and methods: Seventy-five bovine teeth were selected and cut. Dentin was exposed from the buccal surface of the crowns with 220 grit sandpaper, and samples were then inserted in transparent acrylic bases (15x10mm). The samples were randomly divided in 3 groups (n=25): G1-Universal adhesive system Scotchbond™ Universal (3M ESPE-USA); G2-Universal adhesive system Peak Universal Bond (Ultradent); G3-Universal adhesive system Tetric N-Bond (Ivoclar Vivadent). The adhesive procedures were carried out according to the instructions of each manufacturer and the restorative procedures were carried out with micro-cylinders (made of Tygon type tubing 0.79x1.5mm) of the composite resin Filtek™ Z350XT-A2 (3M ESPE-USA). The samples were incubated at 37ºC (+/-5ºC) for 24 hours. Adhesive strength was evaluated in a universal test machine by means of the shear test (0.5mm/ min, 500N) and the resulting fracture type was evaluated with a Dinolite digital microscope (x200). The results were analyzed by descriptive statistics (Mean±SD), and inferential statistics by a one-way ANOVA. Results: No statistically significant differences were found between the universal adhesive systems evaluated G1 (14.91±4.76), G2 (16.90±4.11) and G3 (17.34±4.04)/(p=0.114). Conclusions: The shear test resulted in similar values of immediate adhesive strength of the three universal adhesive systems used.